Narração e memória no mangá Adolf, de Osamu Tezuka (1983-1985) - Moraes, Karen Pinho de (2016)
This research has as object of analyze the manga - a Japanese comic story - Adolf, written by Osamu Tezuka, created and originally published in Japan, from 1983 to 1985. The objective of this study is to understand of how the author, felt through his work, while vehicle sensitivity and problematic the social fabric of their own time, moves in his narrative to the decades of 1930 and 1940, during the rise of Nazism in Germany, the Japanese ultra-nationalism militarist and the outbreak of World War II, and builds a memory not only as a struggle against forgetting and repetition of this past, but this is used for the formulation of a future project. The choice of Adolf based on this study, it gave for its ability to express different dimensions and social practices that are contained in this narrative, offering an interesting and rich wealth of perspectives to historical studies. It was possible to identify and bring to light sensitivities, experiences, subjects, values and social practices from the author's worldview